A dynamics association study of gut barrier and microbiota in hyperuricemia - Lv, Qiulan; Zhou, Jun; Wang, Changyao; Yang, Xiaomin; Han, Yafei; Zhou, Quan; Yao, Ruyong; Sui, Aihua (Frontiers in Microbiology, 2023)
Introduction The intricate interplay between gut microbiota and hyperuricemia remains a subject of growing interest. However, existing studies only provided snapshots of the gut microbiome at single time points, the temporal dynamics of gut microbiota alterations during hyperuricemia progression and the intricate interplay between the gut barrier and microbiota remain underexplored. Our investigation revealed compelling insights into the dynamic changes in both gut microbiota and intestinal barrier function throughout the course of hyperuricemia. Methods The hyperuricemia mice (HY) were given intragastric administration of adenine and potassium oxalate. Gut microbiota was analyzed by 16S rRNA sequencing at 3, 7, 14, and 21 days after the start of the modeling process. Intestinal permeability as well as LPS, TNF-α, and IL-1β levels were measured at 3, 7, 14, and 21 days. Results We discovered that shifts in microbial community composition occur prior to the onset of hyperuricemia, key bacterial Bacteroidaceae, Bacteroides, and Blautia exhibited reduced levels, potentially fueling microbial dysbiosis as the disease progresses. During the course of hyperuricemia, the dynamic fluctuations in both uric acid levels and intestinal barrier function was accompanied with the depletion of key beneficial bacteria, including Prevotellaceae, Muribaculum, Parabacteroides, Akkermansia, and Bacteroides, and coincided with an increase in pathogenic bacteria such as Oscillibacter and Ruminiclostridium. This microbial community shift likely contributed to elevated lipopolysaccharide (LPS) and pro-inflammatory cytokine levels, ultimately promoting metabolic inflammation. The decline of Burkholderiaceae and Parasutterella was inversely related to uric acid levels, Conversely, key families Ruminococcaceae, Family_XIII, genera Anaeroplasma exhibited positive correlations with uric acid levels. Akkermansiaceae and Bacteroidaceae demonstrating negative correlations, while LPS-containing microbiota such as Desulfovibrio and Enterorhabdus exhibited positive correlations with intestinal permeability. Conclusion In summary, this study offers a dynamic perspective on the complex interplay between gut microbiota, uric acid levels, and intestinal barrier function during hyperuricemia progression. Our study suggested that Ruminiclostridium, Bacteroides, Akkermansiaceae, Bilophila, Burkholderiaceae and Parasutterella were the key bacteria that play vital rols in the progress of hyperuricemia and compromised intestinal barrier, which provide a potential avenue for therapeutic interventions in hyperuricemia.